Screening for cystic fibrosis‐related diabetes and prediabetes: Evaluating 1, 5‐anhydroglucitol, fructosamine, glycated albumin, and hemoglobin A1c. Issue 8 (2nd October 2019) - Tommerdahl, Kalie L.; Brinton, John T.; Vigers, Tim; Nadeau, Kristen J.; Zeitler, Philip S.; Chan, Christine L.
Abstract: Objective: Dysglycemia is prevalent in cystic fibrosis (CF) but screening with annual oral glucose tolerance tests (OGTT) can be burdensome. We investigated alternate glycemic markers—hemoglobin A1c (HbA1c), 1, 5‐anhydroglucitol (1, 5AG), fructosamine (FA), and glycated albumin (GA)—as screening tests for CF‐related diabetes (CFRD) and pre‐diabetes (CFPD) in youth with CF as defined by the gold‐standard OGTT 2‐hour glucose (2hG). Methods: Youth 10 to 18 years with CF had a 1, 5AG, FA, GA, HbA1c, and 2‐hour OGTT collected. Correlations between all glycemic markers and 2hG were evaluated. Area under the receiver operative characteristic (ROC‐AUC) curves were generated. Optimal cut points for predicting CFPD (2hG ≥ 140 mg/dL) and CFRD (2hG ≥ 200 mg/dL) were determined. Results: Fifty‐eight youth with CF were included (2hG < 140, n = 16; CFPD, n = 33; CFRD, n = 9; 41% male, mean ± SD age 14.2 ± 3.6 years, BMI z ‐score 0.0 ± 0.8, % predicted forced expiratory volume in 1 second [FEV1] 89.9 ± 15.1, % predicted forced vital capacity [FVC] 103.2 ± 14.6). ROC‐AUC's for all alternate markers were low for CFPD (0.52‐0.67) and CFRD (0.56‐0.61). At a cut point of 5.5%, HbA1c had 78% sensitivity (95% CI: 0.45‐0.94) and 41% specificity (95% CI: 0.28‐0.55) for identifying CFRD, correlating to a ROC‐AUC of 0.61 (95% CI: 0.42‐0.8). Conclusions: All alternate markers tested demonstrate poor diagnostic accuracy for identifying CFRD by 2hG.